2007
DOI: 10.1002/jbm.b.30732
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative biorelevant profiling of material microstructure within 3D porous scaffolds via multiphoton fluorescence microscopy

Abstract: This study presents a novel approach, based on fluorescence multiphoton microscopy (MPM), to image and quantitatively characterize the microstructure and cell-substrate interactions within microporous scaffold substrates fabricated from synthetic biodegradable polymers. Using fluorescently dyed scaffolds fabricated from poly(DTE carbonate)/poly(DTO carbonate) blends of varying porosity and complementary green fluorescent protein-engineered fibroblasts, we reconstructed the three-dimensional distribution of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 116 publications
(177 reference statements)
0
8
0
Order By: Relevance
“…The 2‐D pDTEc films (2‐D Film s) were prepared by spincoating, as described previously (28). Three‐dimensional macroporous pDTEc (3‐D Porous ) scaffolds with bimodal pore size distribution were fabricated by salt leaching and rapid, selective solvent crystallization, as described previously (29). Two types of microfibrous scaffolds were fabricated with different fiber diameters by electrospinning, similar to previously described methods (27).…”
Section: Methodsmentioning
confidence: 99%
“…The 2‐D pDTEc films (2‐D Film s) were prepared by spincoating, as described previously (28). Three‐dimensional macroporous pDTEc (3‐D Porous ) scaffolds with bimodal pore size distribution were fabricated by salt leaching and rapid, selective solvent crystallization, as described previously (29). Two types of microfibrous scaffolds were fabricated with different fiber diameters by electrospinning, similar to previously described methods (27).…”
Section: Methodsmentioning
confidence: 99%
“…Owing to their spectral separation, DAPI/calcein double-stained cells are simultaneously excited at 1000 nm (2-PF of calcein at 500 nm, 3-PF of DAPI at 333 nm). Two-photon fluorescence was used to image and quantitatively characterize the microstructure and cell-substrate interactions within microporous scaffold substrates fabricated from synthetic biodegradable polymers [130]. The authors seeded GFP-labelled fibroblasts in Texas red-labelled poly-(DTE/DTO) carbonate blend scaffolds of varying porosity and studied the spatial distribution of micro-and macroporous regions and cell morphology patterns (e.g.…”
Section: Imaging Of Labelled Structuresmentioning
confidence: 99%
“…[114] Liu et al used MPM to characterise their engineered polycarbonate scaffolds and analyse osteoblastic seeding. [115] This study demonstrated how MPM provides greater sample penetration, less photobleaching, and higher signal-to-noise ratio than conventional single photon imaging. Villa et al have shown that in vivo MPM is possible, by using it to monitor integration and ossification of donor-cell impregnated scaffold constructs in mouse calvarial defects.…”
Section: Multi-photon Spectrometrymentioning
confidence: 72%